La loi sur les jeunes contrevenants et les masse-médias - Los, Maria (Criminologie, 1987)
The recent enactment of the Young Offenders Act has ended a long period of the rule of the “parens patriae”, philosophy whereby the juvenile court's task was not to administer just punishment for the offence but to diagnose and treat the underlying problems. The new legislation, which follows the “justice model”, attempts to broaden legal rights of accused juveniles while simultaneously making juvenile law more punitive and more focused on specific criminal offences. The present article looks at the way the Canadian mass media reported on this major historical shift in the juvenile justice philosophy. The overt and hidden messages are analysed and the sources of the prevailing definitions explored. It has been found that the majority of informants represented powerful interest groups and organizations. Moreover, the investigated press reports created an image of fundamental consensus, and the new legislation was presented as being beneficial to the society as a whole. The inherent contradictions in the philosophy underlying the new Act were overlooked in favour of an image of a perfect balance whereby ambivalences of the new approach became transformed into virtues. The article tests a number of hypotheses and offers theoretical interpretations of the findings. The applicability of the consensual functionalist, critical functionalist and Marxist orientations is assessed.